The Symbolic Meaning of Charaters in Wayang Lupit and Slentheng By Ki Entus Susmono - Kuntoro, Adi; Iswidayati, Sri; Triyanto, Triyanto (Catharsis, 2019)
Wayang Lupit and Slentheng are the characters played in Carangan performance by Ki Entus Susmono. The characters are based on Punawakan. This research analyses the visual elements of Wayang Lupit and Slentheng by Ki Entus Susmono. This research uses qualitative method with semiotic approach. The researchers collected the data from observation, interviews, and documentation. The data were validated by triangulation. The analyses of the data were through data reduction, presentation, and verification. The visual analysis of the characters implemented the theories of Ferdinand De Saussure and Roland Barthes. The findings show that: 1) The characters of Wayang Lupit wear Tegalese costumes, which are clothes, black trousers (in some cases wear Sarong), and iket wulung (a head band); 2) The character of Slentheng wears moslem apparel with sarong and kupluk/peci (moslem cap). Besides, the researchers found that the symbolic meaning of Wayang Lupit and Slentheng are reflected through its use of traditional costume. pakaian adat. In the end, this research can become a reference for similar study in the future, specifically for art education study in the future.